Effects of Surface Heating on Coastal Upwelling Intensity. Issue 2 (14th February 2023) - Jung, Jihun; Cho, Yang‐Ki
Abstract: Numerical experiments were conducted to evaluate the effects of surface heating on coastal upwelling intensity. Offshore transport, isopycnal slope, and the sea surface temperature (SST) difference between coastal and offshore regions, which represent the upwelling intensity, were estimated. Surface heating decreases Ekman transport but increases Ekman pumping by changing air‐sea stability conditions. However, offshore transport does not change significantly with surface heating. Our experimental results revealed that the increase in surface heating decreases the isopycnal slope but increases the SST difference. Both the isopycnal slope and SST difference are closely related to the change in the surface boundary layer (SBL). Strong surface heating thins the surface‐mixed layer, which decreases the vertical eddy viscosity. The decreased vertical eddy viscosity thins the SBL and enhances its offshore velocity. The isopycnal slope weakens because of the thin SBL, while the SST difference becomes stronger because of the enhanced offshore velocity despite the same offshore transport. The present study may be relevant to the change in upwelling systems as the increase in surface heating under future global warming. Plain Language Summary: Coastal upwelling that brings deep cold water to the surface significantly impacts the coastal environment. Hence, it is essential to quantitatively evaluate the coastal upwelling intensity. This study provides deeper insights into the process of how surface heating changes coastal upwelling intensity. Offshore transport, isopycnal slope, and the sea surface temperature (SST) difference between coastal and offshore regions were estimated. The results suggest that the isopycnal slope decreases but the SST difference increases as the surface heating increases, while the offshore transport changes little. These results highlight the importance of the change in upwelling intensity with the increase in surface heating under global warming. Key Points: Surface heating decreases Ekman transport, but increases Ekman pumping With surface heating, isopycnal slopes become gentle but sea surface temperature differences between coastal and offshore regions increase The increase in the cross‐shore temperature difference due to faster offshore velocity overwhelms the decrease by net surface heat flux